Health Problems of Third Gender in Naulo Bihani, Pokhara - Tripathi, Krishna Prasad (Janapriya Journal of Interdisciplinary Studies, 2020)
The third gender is in many cultures made up of an individual, considered male at the time of birth, but change on feminine gender role or sexual role when they grow up and vice versa third genders and homosexual are the group of people who are not allowed to talk about their sexual and emotional preferences in public. The study health problems faced by the third gender of Naulo Bihani, Pokhara raises the genuine questions regarding the demographic and health condition of that third gender. All 60 residing there were the sample of data collection through census method by using interview schedule with open and close questions. Observation and KII were done with the management committee of Naulo Bihani, Pokhara, and sister organization of Blue Dimond Society Kathmandu. It attempts to raise consciousness of human rights on the sexual and gender minorities, witness violence, abuse and rape. All the respondents suffered from viral and bacterial diseases; 78.33 percent suffered from protozoa infection. Only fifteen percent respondents were suffered from Syphilis. But no one was suffered from HIV AIDS. They felt social discrimination and tell them Hijara and so on. It is justification to advocate their right in the society so the researcher tried to make a research on the topic.